2020
DOI: 10.1029/2019gl085359
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless Magnetic Reconnection in an Asymmetric Oxygen Density Configuration

Abstract: Combined with the magnetic field, the distribution of charged particles in the inflow region is expected to control the rate of magnetic reconnection. This paper investigates how the reconnection process is altered by a cold, asymmetrically distributed, oxygen population, which is initially located away from the current layer in the inflow regions. A particle‐in‐cell simulation is used to gain further insight into the dynamics of the system. The time evolution of the reconnection process proceeds rapidly compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…They found that O + , as a consequence of being demagnetized, was ballistically accelerated, primarily by the Hall electric field. Simulations by Tenfjord et al (2019) and Kolstø et al (2020) show that for both symmetrically and asymmetrically distributed O + , the reconnection rate is significantly reduced, but not as much as predicted by mass-loading. The authors describe a mechanism where the O + population (and the accompanying electrons) acts as an energy sink on the system, altering the energy partitioning.…”
Section: Heavy Ions and Reconnection Ratementioning
confidence: 87%
“…They found that O + , as a consequence of being demagnetized, was ballistically accelerated, primarily by the Hall electric field. Simulations by Tenfjord et al (2019) and Kolstø et al (2020) show that for both symmetrically and asymmetrically distributed O + , the reconnection rate is significantly reduced, but not as much as predicted by mass-loading. The authors describe a mechanism where the O + population (and the accompanying electrons) acts as an energy sink on the system, altering the energy partitioning.…”
Section: Heavy Ions and Reconnection Ratementioning
confidence: 87%
“…Beyond this, we speculate that asymmetric lobe filling can be expected to create asymmetric O + density conditions near the nightside reconnection site. Recent work by Kolstø et al (2020) using PIC simulations indicate that such conditions can cause asymmetries in the diffusion region and motion of the reconnection site.…”
Section: Discussionmentioning
confidence: 99%
“…Cassak and Shay (2007) proposed a MHD scaling law of the asymmetric magnetic reconnection rate R in steady state depending only on the inflowing plasma density n and magnetic field B values: (Zhang et al, 2016). As a MHD model, Cassak and Shay (2007) neglect all kinetic processes potentially impacting magnetic reconnection (Dargent et al, 2017;Hesse et al, 2013;Kolstø et al, 2020;Tenfjord et al, 2019). Finally, due to the steady state assumption, one can wonder if this model is still applicable in during variations of the external environment, such as during the impact of a plasmaspheric plume.…”
Section: Introductionmentioning
confidence: 99%